(untitled) (Environment & Health, 2019)
The aim of the work is a hygienic estimation of the air pollution condition by fine suspended particular mater (PM10 and PM4) in the city of Zaporozhye. Materials and methods. The measurements of fine suspended particular mater PM10 and PM4 have been carried out since 2012 to 2017 years in the atmospheric air of Zaporozhye. It was used the KANOMAX-3521 aerosol analyzer for measurements. The data processing was performed with the statistical package of the licensed program “STATISTICA® for Windows 13.0” (StatSoft Inc., No. JPZ8041382130FRCN10-J) and the “Microsoft Excel” program. Results. It has been established that PM10 concentrations in the air of Zaporozhye exceed the recommended levels by the WHO guidelines for air quality. The average concentrations of РМ10 in the city - 0.14 ± 0.002 mg / m3, РМ4 - 0.07 ± 0.001 mg / m3, the concentration of РМ10 is 1.2 times higher (p